The Stages Of Culture Shock: The Experience Of First Time Living In Netherlands By Indonesian Students Of Maastricht University - Kristina Laora; Riski Amrina Sari; Lini Fitri; Nurul Hidayati (English Lecturers and Teachers Association (ELTA), 2025)
Culture shock is the part of a cross-cultural understanding issue. It relates with the experiences during the phases of the newcomer to the host culture. The four phases of phases are used to know the process of adaptation. This article uses the four distinct phases: honeymoon, frustration, adjustment, and acceptance of culture shock by Sverre Lysgaard. It is used the qualitative descriptive method to describe the experiences of the subjects in each phase. Two Indonesian students have received the OTS scholarship (Orange Tulip Scholarship) to take one-year study for a master degree in Maastricht University Netherland started from December 2023 until August 2024 become informants. The result showed that they encountered positive aspects in honeymoon phase by exploring the places, food, the architecture and the admiration of the local mindset, the frustration phase showed that they had some challenges in unpredictable weather, less variation food, the high cost of living, the language and the education system. The self-awareness has finally helped them to survive and accept the culture. The help of local and Indonesian friends who live in the Netherlands are also the main support system in adjusting the process. Keywords : Cross-Culture, Culture Shock, phases.